2023
DOI: 10.1002/cam4.6513
|View full text |Cite
|
Sign up to set email alerts
|

Improved long‐term outcomes after innovative preoperative evaluation and conception of precise surgery for gallbladder cancer

Zi‐Yao Jia,
Yi‐Di Zhu,
Xiang‐Song Wu
et al.

Abstract: BackgroundThree‐dimensional visualization preoperative evaluation (3D‐VPE) and enhanced recovery after surgery (ERAS) have been suggested to improve outcomes of cancer surgery in patients, yet little is known regarding their clinical benefit in patients with gallbladder cancer (GBC). We hypothesized that the combination of 3D‐VPE and ERAS would improve the outcome of patients undergoing surgery for GBC.ObjectiveThis study aimed to determine if 3D‐VPE and ERAS can improve the outcomes and overall survival in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…A study of 227 GB carcinoma patients assessed the effect of three-dimensional visualization preoperative evaluation and enhanced recovery after surgery and found that precise surgery improved oncological outcomes. The researchers found that this effect, compared to the control group, showed a higher R0 resection rate (67.4% vs 20.9%) and number of retrieved lymph nodes (26.6 ± 12.6 vs 16.3 ± 7.6%) and better median overall survival (27.4 mo vs 12.7%), 1-year survival (84.4% vs 53.5%) and 3-year survival (29.8% vs 15.1%)[ 97 ].…”
Section: Managementmentioning
confidence: 99%
“…A study of 227 GB carcinoma patients assessed the effect of three-dimensional visualization preoperative evaluation and enhanced recovery after surgery and found that precise surgery improved oncological outcomes. The researchers found that this effect, compared to the control group, showed a higher R0 resection rate (67.4% vs 20.9%) and number of retrieved lymph nodes (26.6 ± 12.6 vs 16.3 ± 7.6%) and better median overall survival (27.4 mo vs 12.7%), 1-year survival (84.4% vs 53.5%) and 3-year survival (29.8% vs 15.1%)[ 97 ].…”
Section: Managementmentioning
confidence: 99%
“…Gallbladder cancer is a rare cancer which are mostly reported as case reports ( 13 , 14 ). Wu et al.…”
Section: Bile Duct Cancer and Gallbladder Cancermentioning
confidence: 99%